IDENTIFICATION OF MESHING STIFFNESS FUNCTION BY MEANS OF FINITE ELEMENT METHOD - Przemysław GRZESICA (Scientific Journal of Silesian University of Technology. Series Transport)
Undoubtedly simulation methods of investigation of dynamic models behavior have some surpluses. Nevertheless, these methods are burdened by some limitations with the effect of significant disagreement between foreseen (by simulation) and an actual behavior of real objects. The source of these divergences for example it could be insufficient accuracy of the meshing stiffness identification.